Intelligent Sensory Evaluation Methodologies and Applications - Ruan, Da; Zeng, Xianyi (Springer Berlin Heidelberg, 2004)
In today's industrial companies, sensory evaluation is widely used in quality inspection of products, in marketing study and in many other fields such as risk evaluation, investment evaluation and safety evaluation.This book collects a number of representative methods on sensory evaluation. The book reports recent research results and provides a state of the art on intelligent techniques-based sensory evaluation in industrial applications. The focus is especially on theoretical/analytical solutions to the problems of real interest in intelligent techniques with applications to engineers and managers of different industrial departments such as production, quality inspection, product design and development and marketing